Study on Barcoding Implementation for Improving Materials Tracking at Construction Site - Pei Xin, Tan; Kasim, Narimah; Zainal, Rozlin; Shareh Musa, Sharifah Meryam; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2021)
Nowadays, inventory management plays a vital role in every organization because ethical inventory management will help reduce costs and increase productivity. Most of the construction industry still manually maintain their materials and they face a lot of problems in their daily operation. Therefore, this study was conducted to identify the advantages, challenges, and improved ways of barcoding implementation for improving materials tracking at the construction site. The area of research scope is selected in Selangor and the research target respondent is G7 main contractors. Respondents from project managers, site managers, architects, contractors, and site supervisors around the state of Selangor will be selected to get the information. In order to achieve the objectives of this study, the study was conducted using quantitative methods for primary data collection. Secondary data is literature review such as academic books, journal articles, reports, and online data source related to the barcoding implementation for improving materials tracking. Data collection results will be analyzed using descriptive methods to obtain the highest frequency and mean score values using SPSS software. The goal of the outcomes of this analysis is to receive input in response to the objectives set. In addition, it is expected that this thesis would help workers in the construction sector to be armed with a range of options and measures that can be taken to incorporate barcoding to enhance material monitoring at the construction site.